A multi-method econometric analysis of SME loan’s impacts on women’s entrepreneurial development in Bangladesh - Roy, Gourav; Das, Bahadur Chandra; Saha, Puja Rani (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
The paper examines how the socio-economic developments of women entrepreneurs in Bangladesh are influenced by small and medium enterprises (SMEs). An equal weighted composite index based on a quantitative cross-sectional survey design was employed on 489 women entrepreneurs borrowing SME loans to meet the objectives. The study employed methodologies such as OLS, quantile regression, bootstrapped regression, standardised beta regression, hierarchical regression, and moderation effects to test the hypotheses and check the robustness. Results indicate that access to loans and adequacy of loans have a positive influence on the socio-economic development of women entrepreneurs. On the other hand, tight credit checks, excessive collateral requirements and lack of institutional support are growth inhibitors, particularly among low-income individuals. The study has significant policy implications in that SME loans are significantly contributing to the socio-economic welfare of the women entrepreneurs, and Loan factors impact mostly, while both age and education imply the variations across the benefits received from the SME loans. This paper adds value to the literature by examining the dynamics between financial inclusion and institutional support in determining the success of women entrepreneurs by leveraging rigorous econometric modelling. The study paves the way to further research and policy development with a focus on the absorption of SME benefits by optimising loan factors and institutional factors, similar to other emerging economies.